The Influence of Work-Life Balance and Job Satisfaction on Employee Performance at UMKM Menteng Jaya - Ganang Roger Mawardi; Suci Ayu Sudari; Yuni Pambreni (Best Journal of Administration and Management, 2025)
This study aims to determine the effect of Work Life Balance and job satisfaction on employee performance at UMKM Menteng Jaya. Employee performance is one of the key factors in increasing productivity and business sustainability, especially in the UMKM sector. This study uses a quantitative approach with a survey method by distributing questionnaires to all employees of UMKM Menteng Jaya, with a total sampling technique of 56 respondents. The data collected were then analyzed using SPSS software version 27. The results of the study showed that Work Life Balance had a significant effect on employee performance. In addition, job satisfaction was also proven to have a significant effect on employee performance. And Work Life Balance and job satisfaction simultaneously have a significant effect on employee performance. This proves that balanced and satisfying human resource management has a major influence on employee productivity in the UMKM sector.